2000
DOI: 10.1016/s0886-3350(00)00426-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventing lens epithelial cell migration using intraocular lenses with sharp rectangular edges

Abstract: The CeeOn 911 silicone IOL, with sharp rectangular optic edges, showed an effect on preventing PCO that was similar to that of the AcrySof IOL. When a discontinuous capsular bend is created by an IOL with sharp optic edges, the bend may induce contact inhibition of migrating LECs regardless of the lens' material composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 10 publications
3
130
0
10
Order By: Relevance
“…7 These designs are pivotal in the prevention of PCO by preventing lens epithelial cell migration. 8 However, ray tracing techniques have indicated that there is greater internal light scattering onto the retina from the sharp IOL edges than those with rounded edges. 9 Recent works, which has realised the importance of the edge surface, have used a textured edge design of the Acrysof IOL with marked improvements in postoperative glare.…”
Section: Discussionmentioning
confidence: 99%
“…7 These designs are pivotal in the prevention of PCO by preventing lens epithelial cell migration. 8 However, ray tracing techniques have indicated that there is greater internal light scattering onto the retina from the sharp IOL edges than those with rounded edges. 9 Recent works, which has realised the importance of the edge surface, have used a textured edge design of the Acrysof IOL with marked improvements in postoperative glare.…”
Section: Discussionmentioning
confidence: 99%
“…This general pattern ties in well with clinical data 18 ; the further delay with the Alcon AcrySof acrylic IOL can be attributed to the well-described barrier effect from the interaction of the capsule and the square edge of this IOL. 10 At day 28 (end point), low-power images revealed that the percentage coverage of the posterior capsule differed between the groups (see Fig. 6).…”
Section: Capsular Bag Modelmentioning
confidence: 94%
“…These designs are manufactured using a range of materials and are likely to influence the progression of PCO because of the physical association with the capsule, creating a barrier effect. 10 However, there remains a significant need to lower the need for capsulotomies, which place a strain on health care resources and cause inconvenience for patients. 11 However, it should not be assumed that a person who does not undergo corrective laser surgery has optimal vision.…”
mentioning
confidence: 99%
“…17 In addition, a sharp posterior edge of the optic has been ascribed to reduce the PCO rate. 18 It is noteworthy that the two types of IOLs implanted in this study are made of acrylic material and both of them have sharp posterior optic edges.…”
Section: Discussionmentioning
confidence: 92%